Take a look at the bright side: Effects of positive body exposure on selective visual attention in women with high body dissatisfaction. (August 2016) - Glashouwer, Klaske A.; Jonker, Nienke C.; Thomassen, Karen; de Jong, Peter J.
Abstract: Women with high body dissatisfaction look less at their 'beautiful' body parts than their 'ugly' body parts. This study tested the robustness of this selective viewing pattern and examined the influence of positive body exposure on body-dissatisfied women's attention for 'ugly' and 'beautiful' body parts. In women with high body dissatisfaction ( N  = 28) and women with low body dissatisfaction ( N  = 14) eye-tracking was used to assess visual attention towards pictures of their own and other women's bodies. Participants with high body dissatisfaction were randomly assigned to 5 weeks positive body exposure ( n  = 15) or a no-treatment condition ( n  = 13). Attention bias was assessed again after 5 weeks. Body-dissatisfied women looked longer at 'ugly' than 'beautiful' body parts of themselves and others, while participants with low body dissatisfaction attended equally long to own/others' 'beautiful' and 'ugly' body parts. Although positive body exposure was very effective in improving participants' body satisfaction, it did not systematically change participants' viewing pattern. The tendency to preferentially allocate attention towards one's 'ugly' body parts seems a robust phenomenon in women with body dissatisfaction. Yet, modifying this selective viewing pattern seems not a prerequisite for successfully improving body satisfaction via positive body exposure. Highlights: Women with high body dissatisfaction looked relatively long at 'ugly' body parts. This selective viewing pattern remained unaffected by positive body exposure. Positive body exposure successfully enhanced body satisfaction.